KONSTRUKSI VERBA BER- + PREPOSISI DENGAN, DALAM BAHASA INDONESIA - Ekawati, Mursia . (Majalah Transformatika, 2009)
Verbs with her- being intransitive ones in bahasa Indonesia have special attitudes. In one hand, the verbs with ber-, the filler of predicate in use, tend to be followed by constituents of nominal category, so that the constructions seen like having structure of P-0, for example: bertanam padi. In other hand, there are verbs with berÂ having noÂ  direct correlation with the constituents of nominal categories, so that these need prepositional phrase (FP) in forming one construction being a structure of accept6mce one, for example: Adik bertengkar dengan temannya. The specification and the tendency of verbs with ber- the filler of predicate for constructing verbs with her- having preposition of dengan will be discussed in this research. Key words: construction, verbs with ber-, prepositional phrase